Alteration of serum copper in Kala-azar patients during SAG therapy - Banerjee, M; Rahman, M; Shamuzzaman, AK; Akhter, S; Deb, K (Mymensingh Medical Journal, 2007)
The abstract of this article is available on the PubMed website Mymensingh Med J. 2007 Jan;16(1):89-93.